Determination of Lipid Derangements in Human Immunodeficiency Virus Patients Undergoing Anti-Retroviral Therapy - Bashir, Qamar; Haroon, Zujaja Hina; Asif, Naveed; Alam Khan, Muhammad Qaiser; Ghani, Eijaz; Jaffar, Syed Raza (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine lipid derangements in HIV-positive patients receiving anti-retroviral therapy (ART).Study Design: Comparative cross-sectional study.Place and Duration of study: Chemical Pathology Department, in cooperation with the Department of Virology at Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Mar 2019 to Mar 2020.Methodology: In this study, two groups were made. In Group-1, lipid profile estimation was done in HIV patients without treatment. In contrast, lipid profile estimation was done after one year of treatment with anti-retroviral drugs in Group-2. Results: One hundred and two HIV-positive subjects were included in our study. Of these patients, 88(86.27%) were males,and 14(13.73%) were females. Independent sample t-test revealed a statistically significant difference (p-value